Biogeography and diversification of bare‐eyes, an endemic Amazonian clade. (21st April 2022) - Carneiro, Lincoln; Burlamaqui, Tibério C. T.; Aleixo, Alexandre; Oren, David C.; Silva, José Maria Cardoso Da
Abstract: Aim: Biotic interchange, speciation and extinction processes drive biotas assembling. However, the evolutionary outcomes of those mechanisms are complex and difficult to discriminate. Here, we investigate how these processes affect avian diversification in tropical forest regions and test the relative roles of vicariant speciation and biotic interchange on the assemblage of Amazonian biota through the reconstruction of the biogeographical history of bare‐eyes using molecular markers. Location: Amazon. Taxon: Phlegopsis (Aves: Thamnophilidae). Methods: We carried out a phylogenetic reconstruction of Phlegopsis based on four mtDNA and nuclear markers of 52 individuals from 21 localities representing all recognized taxa in the genus. We estimated phylogenetic relationships using both gene tree and species tree methods, demographic history, gene flow and divergence time to reconstruct the biogeographical history of the genus. Results: Phylogenetic analyses recovered nine lineages delimited by some of the largest Amazonian rivers. Molecular dating and biogeographical studies showed that (1) most of the diversification in the genus occurred during the Quaternary; (2) vicariance was the most critical biogeographical process driving the history of this group and (3) two lineages are expanding their ranges, with one of them ( P. n. nigromaculata ) crossing the boundaries of areas of endemism. Main conclusions: Our results reinforce the notion that continental biotas are assembled by alternating dispersal and vicariance events. In Phlegopsis, vicariance shaped the distribution and differentiation of most lineages, but one event of post‐speciation dispersal made two lineages sympatric in Western Amazonia. Dispersal events within the Amazon are not random but are constrained by the characteristics of the species that are expanding their ranges and the features of the places that receive such species. Although most of the speciation events of Phlegopsis occurred during the Quaternary, there is no reason to assume that such events were driven by climatic‐vegetation changes associated with the Milankovitch cycles.